High-yield production of 2D crystals by wet-jet milling. Issue 5 (18th July 2018) - Del Rio Castillo, A. E.; Pellegrini, V.; Ansaldo, A.; Ricciardella, F.; Sun, H.; Marasco, L.; Buha, J.; Dang, Z.; Gagliani, L.; Lago, E.; Curreli, N.; Gentiluomo, S.; et al.
Abstract : A novel liquid-phase exfoliation of layered crystals enables the production of defect-free and high quality 2D-crystal dispersions on a large scale. Abstract : Efficient and scalable production of two-dimensional (2D) materials is required to overcome technological hurdles towards the creation of a 2D-material-based industry. Here, we present a novel approach developed for the exfoliation of layered crystals, i.e., graphite, hexagonal-boron nitride and transition metal dichalcogenides. The process is based on high-pressure wet-jet-milling (WJM), resulting in a 2 L h −1 production of 10 g L −1 of single- and few-layer 2D crystal flakes in dispersion making the scaling-up more affordable. The WJM process enables the production of defect-free and high quality 2D-crystal dispersions on a large scale, opening the way for their full exploitation in different commercial applications, e.g., as anode active material in lithium ion batteries, as reinforcement in polymer–graphene composites, and as conductive inks, as we demonstrate in this report.